2019
DOI: 10.1111/iwj.13241
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the local cure rate of hidradenitis suppurativa following wide local excision

Abstract: Wide local excision is the gold standard and only potential curative therapy for recalcitrant hidradenitis suppurativa. However, high recurrence rates persist even post-surgery with little known on the influencing factors for remission. We evaluated the effect of patient, disease, and operative factors on local cure rate of moderate to severe hidradenitis following wide local excision. We performed a retrospective chart review for all patients who had undergone surgical excision of hidradenitis at a university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
4
9
2
Order By: Relevance
“…While recurrence rates after surgical excision reported in the literature range from 6% to 47%, the recurrence rate in our study was low (10%). In our cohort, the median disease‐free interval for sites where a recurrence occurred was 5 months, which is similar to that of other studies . Although sufficient resection of diseased skin is the most important factor in preventing recurrence, more recent reports have suggested that the number of affected regions, location of hidradenitis, and type of surgical reconstruction may also play a role .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While recurrence rates after surgical excision reported in the literature range from 6% to 47%, the recurrence rate in our study was low (10%). In our cohort, the median disease‐free interval for sites where a recurrence occurred was 5 months, which is similar to that of other studies . Although sufficient resection of diseased skin is the most important factor in preventing recurrence, more recent reports have suggested that the number of affected regions, location of hidradenitis, and type of surgical reconstruction may also play a role .…”
Section: Discussionsupporting
confidence: 88%
“…In our cohort, the median disease‐free interval for sites where a recurrence occurred was 5 months, which is similar to that of other studies . Although sufficient resection of diseased skin is the most important factor in preventing recurrence, more recent reports have suggested that the number of affected regions, location of hidradenitis, and type of surgical reconstruction may also play a role . Numerous methods for closure of axillary defects after wide local excision include primary complex closure, healing by secondary intention, STSG, and local flap rearrangement .…”
Section: Discussionsupporting
confidence: 87%
“…However, this study is strengthened by its large sample size. Patient demographics were consistent with those found in the literature 14,24 and thus the results are considered representative of surgical patients with HS. Future studies comparing suture materials may provide additional information to guide standard of care.…”
Section: Limitationssupporting
confidence: 76%
“…Of the 37 articles that reported recurrence data after excision (representing 1840 patients), the recurrence rate was 30% ( n = 554 patients). Three studies reported recurrence by lesion number, with 98 of 371 lesions recurring across these studies (26.4%) [ 21 , 42 , 13 ]. One study reported recurrence by Hurley stage as follows: 3 lesions recurred in Hurley 1 patients (8.1%), 12 lesions recurred in Hurley 2 patients (32.4%), and 22 lesions recurred in Hurley 3 patients (59.5%) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%